2021
DOI: 10.1016/j.redox.2021.102208
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel neutrophil very long chain plasmalogen molecular species and their myeloperoxidase mediated oxidation products in human sepsis

Abstract: Plasmalogens are a class of phospholipids containing vinyl ether linked aliphatic groups at the sn- 1 position. Plasmalogens are known to contain 16- and 18-carbon aliphatic groups at the sn- 1 position. Here, we reveal that the human neutrophil plasmenylethanolamine pool uniquely includes molecular species with very long carbon chain (VLC) aliphatic groups, including 20-, 22- and 24-carbon vinyl ether linked aliphatic groups at the sn- 1 pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…One mechanism is that loss of plasmalogen is due to oxidative stress during sepsis. We have previously shown plasma 2-chlorofatty acid levels are elevated in human sepsis ( Meyer et al, 2017 ; Amunugama et al, 2021b ). Furthermore, in this rat sepsis model there are increased levels of 2-chlorofatty acid levels ( Pike et al, 2020 ), which is derived from plasmalogens ( Albert et al, 2001 ; Thukkani et al, 2002 ; Amunugama et al, 2021b ).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…One mechanism is that loss of plasmalogen is due to oxidative stress during sepsis. We have previously shown plasma 2-chlorofatty acid levels are elevated in human sepsis ( Meyer et al, 2017 ; Amunugama et al, 2021b ). Furthermore, in this rat sepsis model there are increased levels of 2-chlorofatty acid levels ( Pike et al, 2020 ), which is derived from plasmalogens ( Albert et al, 2001 ; Thukkani et al, 2002 ; Amunugama et al, 2021b ).…”
Section: Discussionmentioning
confidence: 97%
“…We have previously shown plasma 2-chlorofatty acid levels are elevated in human sepsis ( Meyer et al, 2017 ; Amunugama et al, 2021b ). Furthermore, in this rat sepsis model there are increased levels of 2-chlorofatty acid levels ( Pike et al, 2020 ), which is derived from plasmalogens ( Albert et al, 2001 ; Thukkani et al, 2002 ; Amunugama et al, 2021b ). During sepsis the tissue plasmalogen pool or the specific plasmalogen molecular species targeted by HOCl has not been determined.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…On the other hand, the use of state-of-the-art lipidomic techniques elucidated an increasing number of less abundant plasmalogen species. From that, it became evident that next to the most common alcohols used by the alkylglyceronephosphate synthase (AGPS)/glyceronephosphate O -acyltransferase (GNPAT) complex to form the ether bond, i.e., C16:0, C18:0 and C18:1, also C20:0 is relatively common and many others with chain lengths from 16 to 24 carbon atoms, either saturated or with one or two double bonds, can exist ( Amunugama et al, 2021 ; Azad et al, 2021 ). Furthermore, recent studies have shown that, apart from the predominant head groups ethanolamine and choline, also serine and inositol can serve as head group ( Acar et al, 2007 ), whereas the broad range of fatty acyl residues at sn -2 has long been known.…”
Section: Steady State Levels Of Plasmalogens In Health and Diseasementioning
confidence: 99%